Enhancing waste management efficiency through devops application development - Denny Jean Cross Sihombing (Institute of Computer Science (IOCS), 2023)
DevOps is an application development methodology that has been successfully applied in the context of waste management. This research aims to investigate the potential of DevOps implementation in developing waste management applications, emphasizing improving operational efficiency, reducing costs, and regulatory compliance. By collecting data on waste volume, operating costs, and compliance levels, this research shows that the application reduced operating costs by 18% while improving operating efficiency and achieving high compliance with applicable regulations. These findings confirm the significant potential of DevOps in benefiting the waste management industry and its contribution to supporting environmental sustainability. In addition, this research identifies further research possibilities to explore the adaptation and development of applications using more specific DevOps approaches, as well as the scalability of implementation in various organizational contexts.